ANALYSIS OF WATER ABSORPTION AND TOTAL CHROME LEACHING TEST USING ATOMIC ABSORPTION SPECTROPHOTOMETER (AAS) ON PAVING BLOCK SAMPLES MADE FROM WASTE LEATHER SHAVING - Warmiati; Septiyana Windiastuti (Politek ATK Yogyakarta Press, 2023)
Shaving waste from leather tanning can be utilized as a filler material in the production of concrete blocks. The manufactured concrete blocks are subsequently subjected to immersion for durations of 1, 3, 7, 10, and 14 days. Subsequently, the leached total chromium content from the soaked concrete blocks is tested using an atomic absorption spectrophotometer, by the Indonesian National Standard (SNI) 6989-84:2019, which outlines the procedure for testing dissolved and total metal content through atomic absorption spectrometry. Additionally, water absorption testing is conducted according to SNI 03-0349:1989 for concrete blocks used in wall construction. The aim of this research is twofold: to determine the water absorption capacity of three sample variations and compare the results against the SNI, and to ascertain the leached chromium concentration from the soaked blocks over a time range of 1 to 14 days, using an atomic absorption spectrometer and referring to the established environmental quality standards. The results obtained from testing the total chromium content released from the soaked concrete blocks meet the requirements of the quality standards for chromium content in leather tanning wastewater, as specified in Ministerial Regulation No. 5 of 2014 (maximum of 0.6 mg/L) and Local Regulation of Yogyakarta Special Region No. 7 of 2016 (maximum of 0.5 mg/L). Meanwhile, the water absorption testing outcomes for the concrete block samples derived from shaving waste comply with the stipulations of SNI 03-0349:1989. Sample codes A and B meet the criteria for quality level 1, with a maximum absorption of 25%, while sample code C meets quality level II standards.